2022
DOI: 10.3390/cancers14051101
|View full text |Cite
|
Sign up to set email alerts
|

Are Transcription Factors Plausible Oncotargets for Triple Negative Breast Cancers?

Abstract: Breast cancer (BC) is the most diagnosed cancer worldwide and one of the main causes of cancer deaths. BC is a heterogeneous disease composed of different BC intrinsic subtypes such as triple-negative BC (TNBC), which is one of the most aggressive subtypes and which lacks a targeted therapy. Recent comprehensive analyses across cell types and cancer types have outlined a vast network of protein–protein associations between transcription factors (TFs). Not surprisingly, protein–protein networks central to oncog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 162 publications
(241 reference statements)
2
8
0
Order By: Relevance
“…It is made colored). This discovery is consistent with the transcription profiling data reported in various cancer types [30][31][32][33][34], including HCC [31,35]. Recognizing the significant role of TFs in the progression of liver cancers [38][39][40][41][42], we conducted enrichment analyses to unveil the signaling pathways in which the identified TFs are implicated in the context of CCA.…”
Section: Some Diagnostic/prognostic Biomarkers Act As Tfs To Regulate...supporting
confidence: 83%
See 1 more Smart Citation
“…It is made colored). This discovery is consistent with the transcription profiling data reported in various cancer types [30][31][32][33][34], including HCC [31,35]. Recognizing the significant role of TFs in the progression of liver cancers [38][39][40][41][42], we conducted enrichment analyses to unveil the signaling pathways in which the identified TFs are implicated in the context of CCA.…”
Section: Some Diagnostic/prognostic Biomarkers Act As Tfs To Regulate...supporting
confidence: 83%
“…Hence, mutated or improperly regulated TFs in different cancers serve as clear targets for therapeutic drugs as well as diagnostic and prognostic biomarkers [28,29]. Numerous new prognostic biomarkers or biomarker combinations derived from TFs have been identified through comprehensive omics analyses of transcription profiles across different cancer types [30][31][32][33][34], including HCC [31,35]. As numerous cases of liver cancer arise from chronic health conditions like cirrhosis triggered by hepatitis B or hepatitis C infections [18][19][20]22,23,[36][37][38], alterations in gene expression induced by viruses have been documented at both the DNA and RNA levels [38][39][40][41][42].…”
Section: Introductionmentioning
confidence: 99%
“…Another relevant gene is BRCA1/2, which plays an important role in DNA double-strand break repair and DNA stability. It has been observed that the BRCA1 gene can be inactivated epigenetically in TNBC by promoter methylation, conferring poor prognosis [14,15]. Regarding the Phosphoinositide-3-kinase (PI3K)/AKT/Mammalian target of rapamycin (mTOR) pathway, TNBC commonly presents PTEN mutations, whereas mutations in PI3KCA are less frequent.…”
Section: Introduction 1the Crispr System: How It Workmentioning
confidence: 99%
“…Moreover, it has been described that 45% of the BRCA1-mutated TNBCs also harbour MYC amplification. Finally, the transcription factor FOXC1 is highly overexpressed in TNBC, where it has been reported to induce survival, proliferation, epithelial-to-mesenchymal transition (EMT), metastasis, invasiveness, and chemoresistance [14,17,18].…”
Section: Introduction 1the Crispr System: How It Workmentioning
confidence: 99%
“…In particular, the SOX proteins SOX 9, SOX 10, SOX 2, SOX 4, SOX 8 and SOX 11 are reported to be overexpressed in TNBC. However, effective inhibition of these TFs remains elusive because of the absence of binding pockets and intracellular localization [ 12 , 13 ]. Meanwhile, scientific advancement has drawn attention to the development of vaccination strategy using these transcription factors.…”
Section: Introductionmentioning
confidence: 99%